Analisis Kepemimpinan Perempuan Perspektif Dan Perbincangan Terkini Dalam Hukum Islam - Ayatullah; Syaefullah (Yayasan Cendekia Gagayunan Indonesia, 2024)
The purpose of this study is to explore in depth the concept of women's leadership from the perspective of Islamic law. The aim is to provide a clear understanding of Islamic guidelines regarding women's leadership and its limitations. Leadership is understood as behavior that aims to influence the activities of group members in order to achieve a common goal, designed to benefit both individuals and organizations. This study is a literature review using a descriptive-analytic method with a historical-philosophical approach, combining data analysis and documentation verification to ensure valid results. The findings show that women's leadership, from the perspective of Islamic law, is a flexible concept that continues to dialogue with the changing times. Islamic law does not provide strict or definitive practical guidelines regarding women's leadership, as this issue falls under mu'āmalah (human social relations), which requires further elaboration through ijtihad (independent reasoning) and humanitarian considerations. Based on this reasoning, there is no textual or contextual prohibition against women taking on leadership roles. Moreover, leadership is not inherently gendered, as gender is only a difference in identity. Gender refers to the differences between men and women in terms of social, cultural, psychological, and other aspects, which are always related to equal rights between men and women.